Alcohol 'use' and 'abuse': when culture, social context and identity matter: Alcohol 'use' and 'abuse'. (June 2020) - Lo Monaco, Grégory; Bonetto, Eric; Codaccioni, Colomba; Araujo, Marcos Vinicius; Piermattéo, Anthony
Graphical abstract: Highlights: Alcohol consumption is rooted in culture and traditions. Drinking behaviors are culturally regulated, justified and prescribed. Contexts influence drinking behavior perceptions, judgement towards consumers. They have an impact on the labelling of consumer behavior as 'use' and 'abuse'. Alcohol consumption plays a role in the social categorization. Abstract : Alcohol is an ancestral beverage. Both divinized and demonized, it is nowadays at the heart of a great controversy at health and social levels. Its consumption is subject to great control, consumption thresholds are instituted (i.e. WHO), limits imposed. However, it must be admitted that the consumption of alcohol is regulated by culture, contexts and identity. This article aims to show that the terms 'use' and 'abuse' conventionally mobilized to speak of good and bad consumption are not able to exhaust the range of possibilities in terms of alcohol drinking behaviors understanding. Indeed, only the consideration of contextual and identity dynamics can allow us to understand with accuracy the relationship to this substance.